Do the Environmental, Social, and Governance (ESG) Affect Financial Performance: Empirical Study at Indonesian Manufacturing Firm’s - Yenni Khristiana; Kurnia Nur Halimah; Saut Aleksius Siregar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the effect of environmental, social, and governance (ESG) information on the financial performance of 11 manufacturing firms listed on the Indonesia Stock Exchange (2018–2023) with ESG scores from Refinitiv. Using a quantitative approach and panel data regression via Stata, the findings show that individually, ESG components have a negative and insignificant effect, while the overall ESG score has a positive but also insignificant effect on financial performance. Simultaneously, ESG has a positive impact. The model explains 11.18% of the variation in financial performance, with the remaining 88.82% influenced by other factors.